STUDI KEMANTAPAN LERENG LOW WALL DAN DISPOSAL IPBF PERTAMBANGAN BATUBARA PT BUKIT MAKMUR MANDIRI UTAMA - Jexen Ferdianto; Uyu Saismana; Romla Noor Hakim; Sudarmaji Sudarmaji (Geosapta, 2017)
This thesis carried out at the site of the Low wall Pit Paringin and Disposal IPBF PT Bukit Makmur Mandiri Utama (BUMA) Job Site Adaro district tabalong South Kalimantan. This study aims to analyze Slope stability is very important influence on the mining activity that involves excavation and backfilling activities excavated material. In the mining work safety is important for workers, building and mechanical equipment around the Slopes of the Slopes in a safe environment, it can disrupt the smooth production resulting failure to achieve planned production targets and hurt the company.The method used in this research is the method of Bishop with the help of software, graphical methods Hoek and Bray, and analyze the factors affecting the stability of the Slope that led to the Slope in an unstable state or landslides.On the Low wall pit Paringin after analysis in the field obtained value of the safety factor of 1.1 in which the location is not stable then performed repeated analysis so that the Slope is stable then do a re-design in addition to cut the rest of the avalanche and also makes the Slopes in a stable condition, the results of the re obtained value-design safety factor of 1.4 the value of re-designs obtained in compliance with the declared stable because according to the standard PT Adaro is ≥1.2.  For backfilling material OB on disposal IPBF, based on consideration of existing data it will be adding a heap on Disposal IPBF ie RL 96 and RL 108 and will be made mud pool at the RL 108, RL 96 value Safety Factor 1.6 and the geometry RL 108 mud baths Safety Factor value of 1.4. From the results of re-design on the Slopes of the Low wall and Disposal Pit Paringin IPBF obtained value Safety Factor Safety Factor ≥1.2 where value meets the provisions of the Kata-kata kunci: Lereng Tambang, Penanganan, Faktor Keamanan.